2020
DOI: 10.3390/su12125004
|View full text |Cite
|
Sign up to set email alerts
|

Managing a Sustainable and Resilient Perishable Food Supply Chain (PFSC) after an Outbreak

Abstract: It is a challenging task to manage a perishable food supply chain (PFSC), due to the product’s short lifetime and to demand uncertainty. Even worse is the fact that, because of the multitude of participating stakeholders in production, distribution, and retailing, the PFSC becomes complex and thus particularly vulnerable to crises. Product shortages that result from an outbreak like COVID-19 often cause customers to seek alternative sources of supply, possibly with a larger purchasing amount (i.e., hoarding), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 43 publications
0
62
0
1
Order By: Relevance
“… I20 Supply chain vulnerability SC vulnerability is the susceptibility or exposure to a disruptive event in the supply chain Blackhurst et al (2018) ; Azadegan et al (2020) ; Viljoen & Joubert (2018) ; Nakatani et al (2018) ; Konig & Spinler (2016) ; Chowdhury & Quaddus (2016) ; Chen et al (2015 b); Ethirajan et al (2020) . I21 Sustainability Sustainability in the SC is defined as managing the supply chain functions aligned with the social, environmental, and economic sustainability requirements of the stakeholders to reduce sustainability risks in supply chain and improve market performance Seuring & Müller (2008) ; Sharifi et al (2020) ; Chatterjee & Layton (2020) ; Chen et al (2020) ; Handfield et al (2020) ; Zhu & Krikke (2020) ; Kamble et al (2020) ; Niu et al (2020) ; Quayson et al (2020) ; Ivanov (2020) ; Shareef et al (2020) ; He et al (2020) ; Nayak & Dhaigude (2019) ; Maiyar & Thakkar (2020) . I22 Uncertainty “Uncertainty” refers to a state that cannot be directly expressed by a certain amount of information, which describes a situation that cannot be ascertained, or where there are different possibilities.…”
Section: Resultsmentioning
confidence: 99%
“… I20 Supply chain vulnerability SC vulnerability is the susceptibility or exposure to a disruptive event in the supply chain Blackhurst et al (2018) ; Azadegan et al (2020) ; Viljoen & Joubert (2018) ; Nakatani et al (2018) ; Konig & Spinler (2016) ; Chowdhury & Quaddus (2016) ; Chen et al (2015 b); Ethirajan et al (2020) . I21 Sustainability Sustainability in the SC is defined as managing the supply chain functions aligned with the social, environmental, and economic sustainability requirements of the stakeholders to reduce sustainability risks in supply chain and improve market performance Seuring & Müller (2008) ; Sharifi et al (2020) ; Chatterjee & Layton (2020) ; Chen et al (2020) ; Handfield et al (2020) ; Zhu & Krikke (2020) ; Kamble et al (2020) ; Niu et al (2020) ; Quayson et al (2020) ; Ivanov (2020) ; Shareef et al (2020) ; He et al (2020) ; Nayak & Dhaigude (2019) ; Maiyar & Thakkar (2020) . I22 Uncertainty “Uncertainty” refers to a state that cannot be directly expressed by a certain amount of information, which describes a situation that cannot be ascertained, or where there are different possibilities.…”
Section: Resultsmentioning
confidence: 99%
“…One study ( Yuen et al, 2020 ) explored the causes of such panic buying and found that several factors, such as perceived threats, fear of the unknown, the copying of others’ behavior, and other social psychological factors are in play. As a solution, one study ( Zhu and Krikke, 2020 ) suggests that information that may lead to panic buying should not be disseminated to the public. At the same time, non-essential products have seen downward demand, because the income of customers has declined and they prefer to save money for an uncertain future ( Abhishek et al, 2020 , Chiaramonti and Maniatis, 2020 ).…”
Section: Analyzing the Reviewed Articles On The Covid-19 Pandemic In mentioning
confidence: 99%
“…In particular, small fluctuations in downstream demand correspond to amplified swings in upstream demand. Considering the effects of COVID-19 on food supply chains, the spike in demand for some categories of goods affects the correctness of the forecasts of the supply chain actors furthest from the final demand ( Zhu and Krikke, 2020 ). Producers of the goods most in demand during the lockdown, for example, could react by using flexibility tools that increase production to absorb demand and prepare adequate stock levels.…”
Section: Long Run Changesmentioning
confidence: 99%